Green ear yield and grain yield of maize cultivars in competition with weeds - Silva,P.S.L. (2010)
The reduction in herbicide use is one of the greatest interests for modern agriculture and several alternatives are being investigated with this objective, including the adoption of cultivars that suppress weeds. The objective of this study was to verify if maize cultivars develop differently, in competition with weeds, to produce green ears and grain. Randomized complete block design was used, with split-plots and five replications. Cultivars DKB 390, DKB 466, DKB 350, AG 7000, AG 7575 and Master, were evaluated in the plots, without weeding and two weedings (at 22 and 41 days after sowing) in sub plots. Twenty-one species were identified in the experimental area, the most frequent being Gramineae (Poaceae), Euphorbiaceae, Leguminosae (Fabaceae) and Convolvulaceae species. There was no difference in the dry biomass above-ground part of the weeds in the plots of the evaluated cultivars. The cultivars behaved similarly in treatments with or without hoeing, except for plant height and ear height evaluations. Without hoeing, plant height increased in cultivar DKB 390, while plant height and ear height decreased in cultivar AG 7575. In the other cultivars, these traits did not change under weed control. The presence of weeds decreased the values of all traits employed to assess green corn yield, with the exception of the total number of green ears and grain yield.